Past truth & present poetry medical discoveries and the people behind them - Bing, Richard J., 1909-2010 (Tfm Pub., 2006)
Comprises 28 small chapters focusing on medical scientists and their discoveries. This book is of interest to those in medicine who have an interest in the history of outstanding medical discoveries and the individuals behind them.